[Book review] Elizabeth Walgenbach, Excommunication and Outlawry in the Legal World of Medieval Iceland - Nilsson, Bertil (Journal of Northern Studies, 2024)
Review of: Elizabeth Walgenbach, Excommunication and Outlawry in the Legal World of Medieval Iceland (The Northern World 92), Brill: Leiden & Boston 2021